Assessment of mechanical properties of high strength concrete (HSC) after exposure to high temperature - Drzymała, Tomasz; Jackiewicz-Rek, Wioletta; Gałaj, Jerzy; Šukys, Ritoldas (Journal of Civil Engineering and Management, 2018)
There has been a tendency to design ever slender building construction using high strength concrete in recent years. Application of HSC is also growing in tunnel construction. One of the most important challenges is to control explosive spalling of concrete and the method recommended by Eurocode 2 (EN 1992-1-2:2008/NA:2010P) is addition of polypropylene fibres to the mix. The purpose of the research described in this paper was to evaluate the changes of mechanical properties of HSC exposed to the effect of high temperature. The tests were carried out on three types of high strength concrete: air-entrained concrete, polypropylene fibre-reinforced concrete and reference concrete having constant water/cement ratio. The properties of hardened concrete including compressive strength, tensile splitting strength, flexural strength and E-modulus were studied. The latter tests were carried out on both on concrete cured at 20 °C and concrete subjected to high-temperature conditions at 300 °C, 450 °C and 600 °C. The results enabled us to evaluate the effect of high-temperature conditions on the properties of high-performance concrete and compare the effectiveness of the two methods designed to improve the high-temperature performance of the concrete: addition of polypropylene fibres and entrainment of air.